Complete ASP.NET core and entity framework development - Williams, Trevoir (Packt Publishing, 2024)
Embark on a journey to master ASP.NET Core and Entity Framework, the key technologies for developing dynamic web applications. The course begins with an introduction to ASP.NET Core, offering you a solid foundation in .NET and its modern framework. You'll progress through detailed sections covering essential concepts like MVC architecture, environment setup, and source control management with GitHub. As you advance, the course delves into critical areas such as database setup using Entity Framework, service layer implementation, and user authentication. Each module builds on the previous one, ensuring a cohesive learning experience that prepares you for real-world application development. The content is structured to enhance your understanding with hands-on activities, ensuring you can apply what you've learned to practical scenarios. Finally, the course takes you through advanced topics like deploying your applications to IIS and Microsoft Azure, optimizing your applications for different environments. By the end, you'll have developed a full-fledged ASP.NET Core application, equipped with all the skills necessary to tackle complex projects and succeed in the competitive field of web development.
Online resource; title from title details screen (O'Reilly, viewed August 19, 2024)
Keywords: Microsoft .NET Framework; Application program interfaces (Computer software); Interfaces de programmation d'applications; APIs (interfaces); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet